2016
DOI: 10.1038/srep26209
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant functional brain connectome in people with antisocial personality disorder

Abstract: Antisocial personality disorder (ASPD) is characterised by a disregard for social obligations and callous unconcern for the feelings of others. Studies have demonstrated that ASPD is associated with abnormalities in brain regions and aberrant functional connectivity. In this paper, topological organisation was examined in resting-state fMRI data obtained from 32 ASPD patients and 32 non-ASPD controls. The frequency-dependent functional networks were constructed using wavelet-based correlations over 90 brain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 59 publications
(76 reference statements)
3
17
0
Order By: Relevance
“…In line with rsFC studies in adolescents (Aghajani et al, 2016(Aghajani et al, , 2017Cohn et al, 2015) and adults (Philippi et al, 2015;Tang et al, 2016), cases exhibited increases in rsFC with higher CU traits. Callousness and uncaring behavior were related to rsFC patterns including clusters in the precentral gyrus, which has been previously linked to altered rsFC in adolescents with CU-related traits (Cohn et al, 2015;Pu et al, 2017) and psychopathic adults (Espinoza et al, 2018;Korponay et al, 2017;Philippi et al, 2015;Tang et al, 2016). A recent meta-analytic review found that the right anterior insula was implicated in the evaluation of feelings and the left anterior insula in the expression of anger (Lindquist, Wager, Kober, Bliss-Moreau, & Barrett, 2012).…”
supporting
confidence: 70%
See 2 more Smart Citations
“…In line with rsFC studies in adolescents (Aghajani et al, 2016(Aghajani et al, , 2017Cohn et al, 2015) and adults (Philippi et al, 2015;Tang et al, 2016), cases exhibited increases in rsFC with higher CU traits. Callousness and uncaring behavior were related to rsFC patterns including clusters in the precentral gyrus, which has been previously linked to altered rsFC in adolescents with CU-related traits (Cohn et al, 2015;Pu et al, 2017) and psychopathic adults (Espinoza et al, 2018;Korponay et al, 2017;Philippi et al, 2015;Tang et al, 2016). A recent meta-analytic review found that the right anterior insula was implicated in the evaluation of feelings and the left anterior insula in the expression of anger (Lindquist, Wager, Kober, Bliss-Moreau, & Barrett, 2012).…”
supporting
confidence: 70%
“…The DMN seed-based rsFC patterns reported here might suggest uncaring and callousness dimension-specific alterations in (affective) selfreferential processes (Andrews-Hanna et al, 2010). Altered rsFC in the DMN was reported in children and adolescents with CU-related traits (Cohn et al, 2015;Pu et al, 2017) and in adult psychopathy (Pujol et al, 2012;Tang, Jiang, Liao, Wang, & Luo, 2013;Tang et al, 2016). The overlapping SN rsFC with a cluster in precuneal and cingulate areas for uncaring and unemotional behavior scores may reflect their behavioral correlation (Kimonis et al, 2008).…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…This showed that betweenness centrality was a more effective parameter since the hub's vulnerability of betweenness centrality method was larger than other methods and the consistency was better. Specifically, betweenness centrality was indeed widely used for hub analysis of brain functional networks [54,14,55], and our study built on these foundations to study the hubs in the FC network.…”
Section: Reorganized Hub Distributions Between Ts and Controlsmentioning
confidence: 99%
“…Functionally connected elements of the brain exhibit similar spontaneous BOLD signal fluctuations at rest (Biswal et al, 1997), which enables one to capture interactions between brain regions in vivo. Within the network framework, the brain is represented as a graph, a mathematical construct consisting of a set of nodes connected by edges (Grayson et al, 2017;Hagmann et al, 2008;Supekar et al, 2013;Tang et al, 2016). The nodes are defined as anatomical regions of the brain; the edge between each pair of nodes is estimated as the magnitude of association between their BOLD time series (Hagmann et al, 2008;Magalhaes et al, 2015;Paldino et al, 2019;Rubinov et al, 2010;Zalesky et al, 2010).…”
Section: Introductionmentioning
confidence: 99%